Conversion of β-glycopyranoside to α-glycopyranoside by photo-activated radical reaction. Issue 23 (8th June 2016) - Lai, Yu-Chen; Luo, Chin-Hung; Chou, Hsin-Chun; Yang, Cheng-Jhang; Lu, Le; Chen, Chien-Sheng
Graphical abstract: Highlights: Invert the glycosidic bond by photo-activated chlorine radical. Chlorine radical generated from carbon tetrachloride is more active than that from NCS with BF3 ·OEt2 as Lewis acid. Quasi anomeric effect is applied to explain α-regioselectivity for radical anomeric inversion. Abstract: By using carbon tetrachloride as the chloride radical and boron trifluoride etherate as the Lewis acid, the halogen-light-activated anomeric inversion of glycoside was achieved. This reaction is a novel guide to invert the glycosidic bond from a β-anomer to an α-anomer.